Promosi dan Keragaman Produk terhadap Keputusan Pembelian Konsumen pada Minimarket - mujari mujari (IPM2KPE, 2021)
This study aimed to determine the effect of promotion, product diversity, and both of them on consumer purchasing decisions at minimarkets. Primary data in this study were obtained by distributing questionnaires to 70 Minimarket consumers. The data analysis technique used was the SPSS version 23.0 application, using data testing and statistical testing. The results showed that the increase in the promotion variable, the variety of products affected purchasing decisions Keywords: Purchasing Decisions, Product Diversity, & Promotion